Impact of the adoption of Brachiaria grasses: Central America and Mexico - Holmann, Federico J.; Rivas Ríos, Libardo; Argel M., Pedro J.; Pérez, E. (2004)
Livestock production plays a key role in tropical Latin America in a changing economic environment. This study focuses on documenting the transformations of extensive production systems by using superior forage germplasm supplied by regional research systems.